ANALISIS DAN PERANCANGAN SISTEM INFORMASI REKAM MEDIS PADA KLINIK AKPER KESDAM II/SRIWIJAYA GARUDA PUTIH - Rudolf Sinaga; Nurhadi Nurhadi (Jurnal Manajemen Sistem Informasi, 2016)
Clinic of Akper Kesdam II/Swj Garuda Putih located at RT.12 Desa Suak Kandis KM.17, KecamatanKumpeh Ulu Kabupaten Muaro Jambi. Currently patient enrollment, there was a queue when the numberof patients who will be treated to increase, due to the manual search of medical records still are lookingfor in the storage closet that takes about 3-5 minutes. In making the report also need the time because thesource of the report used to use paper media. So that the report made no ready when requested by themanager. Source reports can also be lost, the impact generated report becomes inaccurate. Based on theabove problems, the solution is made is to design and build applications that can help manage patientdata and preparing reports on Clinic of Akper Kesdam II/Swj Garuda Putih. With this application, isexpected to reduce the queues that accumulate while the number of patients who come increased so as toaccelerate the registration process. This application is also expected to accelerate the creation of reportsrequired by the Clinic of Akper Kesdam II/Swj Garuda Putih.